Colonoscopy outcomes of primary screening negative participants highlight the missed diagnosis problem of colorectal cancer screening: an observational study from Yuexiu district in Guangzhou, China - Liu, Yu; Fang, Yujing; Xu, Yahui; Wang, Shuang; Wu, Yanping; Bai, Kunhao; Bible, Paul W.; Ou, Qingjian; Ye, Meixian; Chen, Jiali; Lu, Meiying; Pan, Zhizhong; et al. (Frontiers in Oncology, 2025)
ObjectiveFalse negatives in colorectal cancer (CRC) screening remained a widespread concern, particularly given the notable incidence of false negative results from fecal immunochemical test (FIT). We aimed to investigate the missed diagnoses resulting from primary screening conducted in China that combined the high risk factor questionnaire (HRFQ) with double FITs.MethodsA retrospective cohort study was conducted in Yuexiu district of Guangzhou. Among 69,809 eligible participants who completed the primary screening between 2015 and 2021, we focused on the analysis of 527 subjects who had negative primary screening but underwent colonoscopy.ResultsThese individuals showed statistically comparable prevalence of overall colorectal neoplasms (CRN), advanced colorectal neoplasms (ACRN), and CRC in comparison with those having positive primary screening results (all P>0.05). When compared with subjects having negative primary screening results but no colonoscopy, screening negative participants with colonoscopy were more likely to be younger, possess higher education levels, and have one risk factor for CRC. A logistic regression analysis demonstrated that the missed diagnoses might attribute to the limited risk predictive ability of HRFQ for non-advanced adenoma (OR[95% CI]: 1.11 [0.98, 1.26]; P = 0.103), advanced adenoma (AA) (0.44 [0.38, 0.50]; P < 0.001), CRC (0.39 [0.29, 0.53]; P < 0.001), CRN (0.66 [0.59, 0.73]; P < 0.001) and ACRN (0.41 [0.36, 0.47]; P < 0.001).ConclusionsSubjects with negative primary screening results but having active screening willingness should consider an earlier colonoscopy due to HRFQ’s limited risk predictive ability for colorectal lesions, highlighting an urgency in re-assessment and improvement of the CRC risk scoring system.